A Practitioner's Guide to The Economic Implications of Custody and Access under the Divorce Act and the Federal Child Support Guidelines - Payne, Julien (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2002)
The following analysis provides a bird's eye view of the economic impact of custody and access dispositions on child support orders granted pursuant to sections 8 and 9 of the Federal Child Support Guidelines. It is written for the benefit of legal practitioners and judges in Québec and provides a succinct but relatively comprehensive review of child support orders under the federal guidelines in cases where each parent has custody of one or more of their children (Guidelines, section 8) or where each parent shares custody of or access to their children not less than forty per cent of the year (Guidelines, section 9). It then proceeds to deal with the priority accorded to child support over spousal support as required by section 15.3 of the Divorce Act. In conclusion, it addresses the implications of child rearing responsibilities in the context of spousal support orders, with particular attention being directed to section 15.2(6)(b) of the Divorce Act. For a more detailed analysis of these issues, readers are referred to the author's electronic book Child Support in Canada, which is reproduced on Quicklaw, at db pdcs (data base Payne's Digests on Child Support).